The species of Grammostola (Araneae: Theraphosidae) from Central Argentina: taxonomy, distribution, and surface ultrastructure of coxal setae - Ferretti, Nelson Edgardo (2011)
Three species of Grammostola (Araneae, Mygalomorphae, Theraphosidae) from central Argentina are redescribed and illustrated. Moreover, their geographic distribution is reported. A new synonymy between G. vachoni Schiapelli and Gerschman 1961 and G. schulzei (Schmidt 1994) n. syn. is proposed. We did not find zones of co-occurrence with the three species but, in several localities, we found two Grammostola species in sympatry. The surface ultrastructure of three types of coxal setae was studied by scanning electron microscopy (SEM). Two morphological types of spiniform setae were found on the coxae. The first type consisted of short and strong piriform setae, with the surface completely covered by ridges, and the second type consisted of long and thinner spiniform setae, with a piriform basal portion. The basal portion of the setae had ridges, the central portion was smooth and the apical zone had numerous short barbs with curved tips. The different types of setae found in these Grammostola species are clearly distinguished, and could be new useful character to diagnose at least these species. In combination with other characteristics, these characters could probably help to solve the problems in other species of this difficult genus if not also other genera.